Interocular Amplitude and Latency Differences of Pattern ERG and Pattern VEP Parameters - Fejes, Imre; Kocsis, Péter Balázs; Benedek, György; Janáky, Márta (Optometry and vision science, 2014)
PURPOSETo determine the normal interocular differences in amplitudes and peak times of the pattern electroretinograms (PERGs) and pattern visual evoked potentials (PVEPs) and to investigate whether the PERG and PVEP parameters correspond in lateral dominance or whether the eye-side distributions of the functional parameters are similar. METHODSThe PERGs and PVEPs were recorded in healthy subjects (N = 77) according to the standards of the International Society for Clinical Electrophysiology of Vision, with the modification of the check size of the PERG to 0.5 degrees. This allows stimulation of the macular ganglion cells and their corresponding visual pathways in healthy subjects. RESULTSComparison of the averaged higher and lower response amplitudes and the shorter and longer response peak times showed significant differences (p < 0.001) in both the PERG and the PVEP parameters (median [5 to 95%])the P50 (1.92% [0 to 5.48%]) and N95 (2.06% [0 to 13.95%]) peak times and the P50 (11.82% [1.32 to 29.93%) and N95 (9.45% [1.17 to 30.38%]) amplitudes of the PERGs and the P100 (1.04% [0 to 4.15%]) and N135 (1.96% [0 to 12.36%]) peak times and the P100 (9.86% [1.26 to 29.76%]) and N135 (11.19% [1.18 to 29.99%]) amplitudes of the PVEPs. No significant correlation was found concerning the eye dominance of the PERG and PVEP parameters. CONCLUSIONSOur results reveal a significant interocular difference on PERG and PVEP recording, but this could not be ascribed to the anatomy of the retina and related visual pathways. If the difference between the eyes is not taken into account, misinterpretation may occur in a pathological process.